THROUGH THE EYES OF LUPUS: LIPAEMIA RETINALIS AS A RARE OCULAR MANIFESTATION OF HYPERTRIGLYCERIDEMIA - Tan, Jia Miao; Bernard, Dorothy Maria Anthony; Foo, Siew Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Lipaemia retinalis is a rare but striking ocular finding caused by extreme hypertriglyceridemia. It is typically associated with primary dyslipidemias but may also occur secondary to autoimmune disease such as systemic lupus erythematosus (SLE). We describe a case of newly diagnosed SLE with lupus nephritis, incidentally found to have lipaemia retinalis, leading to the diagnosis of severe hypertriglyceridemia. METHODOLOGY A 12-year-old female presented with two months of intermittent fever and constitutional symptoms. Investigations revealed normochromic normocytic anemia, raised inflammatory markers, positive ANA (speckled pattern) and anti-dsDNA with low complement levels. Proteinuria was present, and subsequent renal biopsy confirmed class III lupus nephritis. Fundoscopy revealed an incidental finding of lipaemia retinalis, and lipid profile showed severe hypertriglyceridemia with a serum triglyceride (TG) of 11.7 mmol/L. Other secondary causes of hypertriglyceridemia, including hyperglycemia, hypothyroidism, alcohol or dietary fat, were excluded from biochemistry and clinical history. The lipid profiles of first-degree relatives were unremarkable. She was started on high-dose omega-3 fish oil, a very low-carbohydrate diet and fenofibrate 145 mg every other day along with immunosuppression therapy for SLE. Her serum TG dropped markedly to 4.1 mmol/L within 3 weeks. However, she had transient bradycardia leading to temporary cessation of fenofibrate and hydroxychloroquine, and her serum TG rebounded to 16.5 mmol/L. After ruling out other causes of bradycardia, fenofibrate was resumed without recurrence of bradycardia, followed by normalization of the TG level. Fundoscopic examination two months later showed resolution of lipaemic retinalis. She completed six cycles of cyclophosphamide with steroid tapering, and her serum TG remained normal at 0.5 mmol/L. CONCLUSION This case highlights lipaemia retinalis secondary to severe hypertriglyceridemia as a rare manifestation in newly diagnosed SLE. Early recognition, aggressive lipid-lowering therapy, along with immunosuppressive treatment for the underlying SLE led to rapid triglyceride reduction with complete resolution of lipemia retinalis.